Using a modified version of photovoice in a European cross‐national study on homelessness - Gaboardi, Marta (2022)
This study proposes an innovative use of a modified version of photovoice for cross‐national qualitative research that allows participants to express their ideas, experiences, and emotions about a topic through photographic language. We examine factors affecting social service providers' work on people experiencing homelessness in Europe. We highlight five advantages of using photovoice in cross‐national research: visual language, methodological flexibility, participatory data analysis, the bottom‐up process, and the promotion of social change. Moreover, we identify key stages of the process: writing a detailed protocol for the implementation and fidelity of the projects, using two levels of data analysis, and disseminating the results. This study provides lessons learned for others who may want to use photovoice in cross‐national research.